Prioritization of head and neck cancer patient care during the COVID-19 pandemic: a retrospective cohort study - Samuel S. Psycharis; Samer Salameh; Sena Turkdogan; Saad Razzaq; Kevin Zhao; Marco A. Mascarella; Keith Richardson; Alex M. Mlynarek; Michael P. Hier; Nader Sadeghi (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The COVID-19 pandemic placed considerable strain on the healthcare system, leading to the re-allocation of resources and implementation of new practice guidelines. The objective of this study is to assess the impact of COVID-19 guideline modifications on head and neck cancer (HNC) care at two tertiary care centers in Canada. Methods A retrospective cohort study was conducted. HNC patients seen at two tertiary care centers before and after the onset of the COVID-19 pandemic (pre-pandemic: July 1st, 2019, to February 29th, 2020; pandemic: March 1st, 2020, to October 31st, 2020) were included. The pre-pandemic and pandemic cohorts were compared according to patient and tumor characteristics, duration of HNC workup, and treatment type and duration. Mean differences in cancer care wait times, including time to diagnosis, tumor board, and treatment as well as total treatment package time and postoperative hospital stay were compared between cohorts. Univariate and multivariate analyses were used to compare characteristics and outcomes between cohorts. Results Pre-pandemic (n = 132) and pandemic (n = 133) patients did not differ significantly in sex, age, habits, or tumor characteristics. The percentage of patients who received surgery only, chemo/radiotherapy (CXRT) only, and surgery plus adjuvant CXRT did not differ significantly between cohorts. Pandemic patients experienced a significant time reduction compared to pre-pandemic patients with regards to the date first seen by a HNC service until start of treatment ( $$\overline{x}$$ x ¯  = 48.7 and 76.6 days respectively; p = .0001), the date first seen by a HNC service until first presentation at tumor board ( $$\overline{x}$$ x ¯  = 25.1 and 38 days respectively; p = .001), mean total package time for patients who received surgery only ( $$\overline{x}$$ x ¯  = 3.7 and 9.0 days respectively; p = .017), and mean total package time for patients who received surgery plus adjuvant CXRT ( $$\overline{x}$$ x ¯  = 80.2 and 112.7 days respectively; p = .035). Conclusion The time to treatment was significantly reduced during the COVID-19 pandemic as compared to pre-pandemic. This transparent model of patient-centered operative-room prioritization can serve as a model for improving resource allocation and efficiency of HNC care during emergency and non-emergency scenarios.